Short-term effects of cigarette smoking - Golding, J; Golding, J F (1980)
In spite of Health Education campaigns the majority of smokers continue to smoke. This thesis presents some evidence concerning the factors underlying the maintenance of cigarette smoking, in terms of the short term effects of cigarette smoking on a variety of physiological measures of arousal. Both stimulant, depressant and mixed effects of cigarette smoking were demonstrated on a number of physiological variables (EEG, electrodermal and EMG). No consistent effect was found on respiration rate or irregularity. Heart rate was invariably increased by cigarette smoking. Sham smoking accounted for approximately 50% of all effects in both directions (.stimulant or depressant), with the exception of cigarette induced tachycardia which appeared to be entirely accounted for by tobacco smoke inhalation and by implication nicotine. The pre-smoking 'starting-state' of the subject had important consequences as regards the magnitude and direction of smoking effect, stimulant versus depressant. Cigarette smoking tended to produce stimulant effects in subjects with low levels of presmoking physiological arousal CEEG, electrodermal) and depressant effects in subjects exhibiting high levels of pre-smoking arousal. The vigour of smoking style (puffing rate, puff duration and pressure, inhalation) increased during stress and also increased with low nicotine delivery cigarettes. These results are interpreted as supporting an 'Arousal Modulation' model of cigarette smoking, i.e. smokers can use cigarette smoking as a device for controlling their level of arousal towards an 'optimum' by virtue of the biphasic stimulantdepressant dose response of nicotine and to some extent, by virtue of the effects of smoking behaviour in the absence of nicotine.